Influence of Shunt Branch on the Current Limiting and Recovery Performance of Variable Resistance SFCL - Duanjiao Li; Bin Xiang; Congwei Yao; Qi Zhang; Xiaofeng Pang; Wenxing Sun; Haiyun Tang; Xue Zhang; Zhongbin Yuan; Linglong Cai (IEEE Access, 2025)
With the continuous development of power grid, the high short-circuit threatens the stability of the power system. The short-circuit exceeds the disconnection capacity of the circuit breaker and has a negative impact on the integrity and stability of the power grid. Therefore, the research and application of the fault current limiter (FCL) has become particularly important, especially the superconducting fault current limiter (SFCL), which uses the zero resistance characteristics in the superconducting state and shows obvious advantages in the power system. In this paper, the current limiting and recovery performance of a variable resistance SFCL (VR-SFCL) is investigated. A test model is built with a 2 kV/20 kA LC source. The effects of the shunt branch parameters on the current-limiting resistance and recovery time are investigated. And further analysis of a 10 kV/630 A system is made through simulation based on the experimental results. From the test and simulation results, the parallel branch parameters can be designed from the current limiting demand, and the minimum tape length can be calculated from the fitted equation with recovery in 300 ms, which can be used to design VR-SFCL with appropriate tape length.